Algal biodiesel stabilization with lower concentration of 1:3 ratios of binary antioxidants – Key factors to achieve the best synergy for maximum stabilization. (15th February 2018) - Rawat, Devendra S.; Joshi, Girdhar; Pandey, Jitendra K.; Lamba, Bhawna Y.; Kumar, Pankaj
Highlights: Long term storage stability of algal biodiesel is achieved by using binary mixture of antioxidants. Antioxidants have shown the best antioxidants synergy with 1:3/3:1 proportions. Higher concentration of binary antioxidants results low antioxidant synergy. Comparatively lower concentration of binary antioxidants is required to achieve the best synergy and stabilization factor. Abstract: Poor storage stability of biodiesel is considered a major problem for its commercialization. The use of commercial antioxidants has been proven very effective for biodiesel stabilization; hence these are frequently being used for long term storage of biodiesel. Moreover, in comparison to individual antioxidants, use of their binary combinations with their optimized concentrations could be more economical and highly effective to improve the storage behavior of biodiesel. In present report the effectiveness of lower concentration of binary antioxidants on the oxidation stability of algal biodiesel was studied. The 500, 600 and 700 ppm concentrations of binary combinations of three antioxidants [ i.e. Pyrogallol (PY); Propylgallate (PrG) and tert -butyl hydroquinone (TBHQ)], are prepared at weight ratios of 1:1, 1:2, 1:3 and 1:9 and vice-versa. Although, storage stability was increased with increase in antioxidant concentration; however, the best synergy was obtained with 1:3 ratios of binary antioxidants with 500 ppm concentration of binary antioxidants.